Microfinance and SDG 7: financial impact channels for mitigating energy poverty. Issue 8 (17th November 2022) - Manko, Karli; Watkins, Todd A.
ABSTRACT : Energy poverty is a complex challenge, particularly in developing countries. Energy access is a prerequisite for economic development, and its absence perpetuates economic, health, and environmental disparities. The United Nations created SDG 7: "Ensure access to affordable, reliable, sustainable and modern energy, " to guide efforts toward achieving universal energy access. This article assesses the channels through which microfinance impacts SDG 7, identifying three main channels: funding and infrastructure, financial services, and microenterprise development. Each impact channel is supported by case studies of institutions that have utilised microfinance platforms to achieve energy development goals.